(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Anaesthetics of shorter action play pivotal rule in the outcome of Day Case Anaesthesia. Objectives: To evaluate the efficacy of "Ketofol" (ketamine Propofol Combination) for Day Case Anaesthesia. Methods: 1013 adult patients of both sex, age from 18 to 50 years, ASA physical grading I and II were scheduled to undergo different day case surgical procedures at Cantonment Military Hospital, Dhaka, in two calendar years from July 2010 to June 2012 were randomly included in the study. Ketofol (1:1 mixture of ketamine 10 mg/ml and propofol 10 mg/ml) was administered intravenously by using titrated aliquots. All perioperative vital parameters, events, complications, recovery status and doses were recorded and subsequently analyzed. Results: In 1013 patients mean dose of ketofol administered was 0.75 ± 0.14 (mean ± SD) mg/kg body weight, mean procedure time was 31.26 ± 9.37 (mean ± SD) minutes and mean recovery time was 16.27 ± 4.68 (mean ± SD) minutes and mean recovery score (Aldrete recovery score) was 8.29 + 0.25 (mean ± SD). Surgery was successfully done in every patient. Anaesthesia related complications like desaturation (SpO2 less than 93% ), was noted in 21 (2.07%) patients and corrected with supplemental oxygen, misalignment of airway observed in 17 (1.68%) patients and corrected by repositioning, hypotension observed in 6 (0.59%) cases and corrected with crystalloid administration, transient hypertension (systolic BP more than 30% of baseline record) observed in 9 (0.89%) cases and corrected without any measure. During recovery vomiting was reported in 6 (0.59%) patients and agitation was reported 9 (0.89%) patients. Conclusion: Combination of ketamine and propofol in a single syringe to be easy to use and highly effective as an anaesthesia regimen with short recovery time in the day case anaesthesia setting. Few side effects occurred and those were either self-limited or responded to minimal interventions. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 16-21